Redesign Instalasi Sistem Pendingin Bearing Turbine PLTA Tanggari untuk Mengubah Pola Maintenance dari Offline Menjadi Online - Meyer Nixon Nelwan; Salman Salman (Energi & Kelistrikan, 2019)
Hydroelectric power plant is one of the power plants that uses renewable energy sources with a low cost of production, in addition to providing a large enough profit for PLN, it can also be a source of revenue to cover production costs in meeting the system needs, so that the hydropower continues to operate optimally, Currently the Tanggari Hydroelectric Power Plant's special operating pattern can be approved not yet maximally based on the number of maintenance hours reaching 3-5 hours / month, this causes potential losses because most jam hours are carried out during the rainy season Turbine bearing temperature conditions continue to increase considering the poor air conditions associated special problem for hydropower. In this journal the author brings one of the breakthrough ideas to overcome this by implementing the Redesign of the Hydro Turbine Cooling System Installation to facilitate backwashing so that it can change maintenance patterns from offline to online. Implementation results can provide benefits because hydropower no longer needs to perform maintenance on the cooling system with offline mode so that hydropower can operate more optimally.